2014
DOI: 10.1186/s12977-014-0100-1
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of H171T resistance reveals the importance of Nδ-protonated His171 for the binding of allosteric inhibitor BI-D to HIV-1 integrase

Abstract: BackgroundAllosteric HIV-1 integrase (IN) inhibitors (ALLINIs) are an important new class of anti-HIV-1 agents. ALLINIs bind at the IN catalytic core domain (CCD) dimer interface occupying the principal binding pocket of its cellular cofactor LEDGF/p75. Consequently, ALLINIs inhibit HIV-1 IN interaction with LEDGF/p75 as well as promote aberrant IN multimerization. Selection of viral strains emerging under the inhibitor pressure has revealed mutations at the IN dimer interface near the inhibitor binding site.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 69 publications
(125 reference statements)
3
51
0
Order By: Relevance
“…Previous studies on point mutants at amino acid residues critical for INLAI binding to IN, that dramatically decrease IN affinity for INLAIs, showed that both ARV activities were either lost concomitantly in the T174I mutant or both strongly affected, although at variable level in the case of the H171T mutant (12,35). These mutants, the T174I in particular, demonstrate that the two activities of INLAIs are linked to their binding to the LEDGF-binding pocket.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies on point mutants at amino acid residues critical for INLAI binding to IN, that dramatically decrease IN affinity for INLAIs, showed that both ARV activities were either lost concomitantly in the T174I mutant or both strongly affected, although at variable level in the case of the H171T mutant (12,35). These mutants, the T174I in particular, demonstrate that the two activities of INLAIs are linked to their binding to the LEDGF-binding pocket.…”
Section: Discussionmentioning
confidence: 82%
“…These findings have suggested that LEDGF/p75 is able to effectively compete with ALLINIs for binding at the IN CCD dimer interface during the initial steps of virus replication. In contrast, in producer cells, neither depletion nor overexpression of LEDGF/p75 influenced the potency of ALLINIs on subsequent virus infectivity (Jurado et al 2013; Balakrishnan et al 2013; Slaughter et al 2014; Fadel et al 2014). These results indicate that the lack of competition between the inhibitor and LEDGF/p75 during virus assembly enables ALLINIs to potently induce aberrant IN multimerization and impair correct core morphogenesis.…”
Section: Small Molecules Promote Aberrant Higher Order Hiv-1 Integmentioning
confidence: 83%
“…Experiments with LEDGF/p75 knockdown and knockout cells helped to explain these observations (Jurado et al 2013; Wang et al 2012; Schrijvers et al 2012; Balakrishnan et al 2013; Fadel et al 2014; Slaughter et al 2014). ALLINI BI-D potency during the early stages of viral replication increased ~29-fold and ~17-fold in LEDGF/p75 knockdown and knockout cells, respectively (Jurado et al 2013; Slaughter et al 2014). These findings have suggested that LEDGF/p75 is able to effectively compete with ALLINIs for binding at the IN CCD dimer interface during the initial steps of virus replication.…”
Section: Small Molecules Promote Aberrant Higher Order Hiv-1 Integmentioning
confidence: 97%
See 1 more Smart Citation
“…The resistance mutation IN A128T is responsible for an 8.65-to 11-fold change of the EC50 of CX05045 (4) and CX014442 (5), respectively while A128N and L102F induce a 64-and 60-fold change of the EC50 of BI224436 (9). Other single resistance mutations identified are the Y99H, Y99N A129T and H171T 78,86 . Although LEDGINs block early replication at the integration step, no resistance to INSTIs was observed with LEDGIN-resistant viruses.…”
Section: Mechanism Of Inhibitors Targeting the Ledgf/p75mentioning
confidence: 99%